Efficacy of platelet rich plasma in comparison to steroid for the management of chronic plantar fasciitis - Thora, Ankit; Tiwari, Anurag; Bhatnagar, Nishit; Mohindra, Mukul (International Journal of Research in Orthopaedics, 2018)
Background: Chronic plantar fasciitis is often a difficult to treat entity and platelet-rich plasma (PRP) is an upcoming modality instead of steroid in chronic cases of plantar fasciitis resistant to traditional non-operative management. Methods: Sixty patients with chronic plantar fasciitis were prospectively randomised into 2 groups and treated with either a single injection of 3 cc PRP or 40 mg DepoMedrol (Cortisone) injection and followed for a year. Immediately prior to PRP or cortisone injection American Orthopedic Foot and Ankle Society (AOFAS) hind foot scoring was done for all patients. These scores were repeated at 6 weeks, 6 months and 12 months. Results: Six weeks evaluation of AOFAS after PRP and corticosteroid administration, the mean visual analogue scale (VAS Score) showed a significant increase in corticosteroid group (4.2) as compared to PRP group (5.8). But, the PRP group (1.8) showed significant improvement in mean VAS scores as compared to Steroid group (3.4) after a year of the treatment. Similarly, the AOFAS score improved significantly in the steroid group (64.4) at 6wks as compared to the PRP group (52.2) but at 12 months however, the PRP group sustained its effect with a mean AOFAS score of 92.2 while in the steroid group, the score dropped to a mean of 78.4. Conclusions: PRP was more effective than steroid for the long term treatment of chronic plantar fasciitis. Level of Evidence: Level I, prospective randomized comparative series.